2020
DOI: 10.21203/rs.3.rs-45845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How can social media analytics assist authorities in pandemic-related policy decisions? Insights from Australian states and territories

Abstract: Background and objectives: Due to COVID-19, various countries introduced lockdowns and limited citizen movements. These restrictions triggered an increased use of digital technologies and platforms by the public. This provides an opportunity for the authorities to capture public perceptions on COVID-19 from social media channels to make informed decisions. The use of social media analytics during pandemics for decision-making, however, is an understudied area of research. Thus, this study aims to generate insi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The primary selection criterion concerned the social media data availability. We obtained geotagged Twitter messages on COVID-19 from Australia ( n = 96,666), via QUT’s Digital Observatory (Yigitcanlar et al , 2020a). Then, a data cleaning process was employed to obtain the mostly relevant tweets for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The primary selection criterion concerned the social media data availability. We obtained geotagged Twitter messages on COVID-19 from Australia ( n = 96,666), via QUT’s Digital Observatory (Yigitcanlar et al , 2020a). Then, a data cleaning process was employed to obtain the mostly relevant tweets for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Sentiment analysis allows investigating people's sentiments and emotions from texts. For example, three studies [76]- [78] solely focused on extracting the users' polarity from COVID-19 datasets with the aim of building more accurate classification models. All three studies used Twitter datasets extracted in 2020, the year of the worldwide outbreak of COVID-19.…”
Section: ) Threat Perceptionmentioning
confidence: 99%
“…However, only one of the 81 articles reviewed in this scoping review specifically identified Australian users, and Aboriginal and Torres Strait Islander people were not mentioned in this paper. 38 In another scoping review, only five studies examined the impact of social media campaigns on Aboriginal and Torres Strait Islander health. 39 Despite the paucity of studies, Walker et al noted a consistent theme of self-empowerment.…”
Section: Introductionmentioning
confidence: 99%